2021
DOI: 10.1186/s13054-021-03783-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted high mean arterial pressure aggravates cerebral hemodynamics after extracorporeal resuscitation in swine

Abstract: Background Extracorporeal cardiopulmonary resuscitation (E-CPR) is used for the treatment of refractory cardiac arrest. However, the optimal target to reach for mean arterial pressure (MAP) remains to be determined. We hypothesized that MAP levels critically modify cerebral hemodynamics during E-CPR and tested two distinct targets (65–75 vs 80–90 mmHg) in a porcine model. Methods Pigs were submitted to 15 min of untreated ventricular fibrillation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“… 42 As demonstrated in a recent ECPR swine model, a higher MAP target is beneficial to autoregulation during cardiac arrest yet detrimental after arrest. 33 The inability to maintain or control CBF after arrest is associated with worse neurological outcomes, 43 and while the heterogeneity in this study population, with average CBFs from 12% to 296% of baseline values during CPR and 7% to 139% during VA‐ECMO, limits conclusions that can be drawn, an inability to manage CBF attributable to deranged autoregulation likely contributed to injury and deserves further study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 42 As demonstrated in a recent ECPR swine model, a higher MAP target is beneficial to autoregulation during cardiac arrest yet detrimental after arrest. 33 The inability to maintain or control CBF after arrest is associated with worse neurological outcomes, 43 and while the heterogeneity in this study population, with average CBFs from 12% to 296% of baseline values during CPR and 7% to 139% during VA‐ECMO, limits conclusions that can be drawn, an inability to manage CBF attributable to deranged autoregulation likely contributed to injury and deserves further study.…”
Section: Discussionmentioning
confidence: 91%
“…31 , 32 The smaller 10‐kg piglets used in this study created additional challenges in establishing sufficient ECMO pump flow but added value in dedicated study to pediatric anatomy and physiology, with 1‐month‐old piglets having similar neuroanatomy and neurodevelopment to pediatric patients. 25 , 26 Unlike many swine ECPR models that simulate cardiac arrest with low ECLS flow rates, 30 , 33 , 34 this model provided 30 or 60 minutes of chest compressions, leading to various injuries with clinically relevant hemodynamic consequences, such as liver lacerations with intra‐abdominal hemorrhage and rib fractures leading to hemothoraces and pneumothoraces, likely the result of CPR‐related rib fractures or worsened compliance and high peak inspiratory pressures during prolonged CPR.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing the MAP target requires the use of vasopressors that could be deleterious after cardiac arrest. For instance, we have recently demonstrated that MAP target above 80 mm Hg using higher dosage of epinephrine progressively disrupt cerebral autoregulation and brain hemodynamics in swine treated by E-CPR, ultimately counterintuitively deteriorating cerebral hemodynamics (13). That is the reason why ICP decrease could be a better option to increase CePP without additional amounts of vasopressor.…”
Section: Discussionmentioning
confidence: 99%
“…It was evidenced by lower ICP and a trend toward greater CePP and less epinephrine need at the end of the protocol. This is of importance since epinephrine deteriorates cerebral microcirculation after cardiac arrest (13). Conversely, cerebral blood flow was neither ameliorated nor deteriorated by head-up versus flat position.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The available evidence supports a physiology-guided treatment strategy to titrate the resuscitation efforts to patient's physiological response. [21][22][23][24][25][26] The 'personalized physiology-guided resuscitation in highly monitored patients with cardiac arrest' resuscitation strategy 20 was investigated in a RCT (PERSEUS-PS, NCT04428060). Unfortunately, the trial was prematurely terminated due to the COVID-19 pandemic.…”
Section: Editormentioning
confidence: 99%